2017
DOI: 10.1007/s11229-017-1397-9
|View full text |Cite
|
Sign up to set email alerts
|

Is defining life pointless? Operational definitions at the frontiers of biology

Abstract: Despite numerous and increasing attempts to define what life is, there is no consensus on necessary and sufficient conditions for life. Accordingly, some scholars have questioned the value of definitions of life and encouraged scientists and philosophers alike to discard the project. As an alternative to this pessimistic conclusion, we argue that critically rethinking the nature and uses of definitions can provide new insights into the epistemic roles of definitions of life for different research practices. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 92 publications
(104 reference statements)
1
25
0
Order By: Relevance
“…These reflections on the practical implications of scientists' basic concepts of life show that conceptual approaches to life and living matter provide a fundamental framework for current and further scientific research within SB: they have implications for research questions, objectives, and suggested approaches as well as for the assessment of scientific results. Hence, in line with the analyzed contributions of operational definitions [3], it can be stated that the reconstructed heuristics of life have a pragmatic utility in guiding research practices within SB on a general level. As they all imply contrasting explicit or implicit assumptions on the differentiation between living and non-living matter, naturalness and artificiality with regard to the assessment of the generation of synthetic organisms, and between life and living objects the questions arises of whether and to what extent the different conceptual approaches are compatible with each other.…”
Section: Discussionmentioning
confidence: 81%
“…These reflections on the practical implications of scientists' basic concepts of life show that conceptual approaches to life and living matter provide a fundamental framework for current and further scientific research within SB: they have implications for research questions, objectives, and suggested approaches as well as for the assessment of scientific results. Hence, in line with the analyzed contributions of operational definitions [3], it can be stated that the reconstructed heuristics of life have a pragmatic utility in guiding research practices within SB on a general level. As they all imply contrasting explicit or implicit assumptions on the differentiation between living and non-living matter, naturalness and artificiality with regard to the assessment of the generation of synthetic organisms, and between life and living objects the questions arises of whether and to what extent the different conceptual approaches are compatible with each other.…”
Section: Discussionmentioning
confidence: 81%
“…This more complex approach, instead, acknowledges the operational role of theoretical considerations and of definitions as guidelines for the design of experiments and models (Bich and Green, 2018). In this case concepts and definitions are not used as sources of checklists or tests for life or cognition (demarcation criteria), but in combination with other types of criteria, such as relevance and successful design.…”
Section: Conclusion: Evaluation Strategiesmentioning
confidence: 99%
“…The same can be said about definitions of cognition.16 Definitions are not necessarily (definitive) answers, but rather ways to formulate precise questions. In the practice of several disciplines such as synthetic biology, artificial life, systems biology, and astrobiology, definition are used as theoretical and epistemic tools that make assumptions explicit, clear, and challengeable, help formulating questions, and suggest what phenomena to look for, or what to realize in the laboratory(Bich and Green, 2018). Definitions of life are not normally used as definitive answers and tools to demarcate life.…”
mentioning
confidence: 99%
“…A necessary step in this direction is to discuss what biological communication is and what types of phenomena and interactions it includes. The aim is to provide an operational account [8] capable of grounding and orienting theoretical and experimental research on communication in synthetic biology, and of offering guidelines for the evaluation of results. This account should be able to provide conceptual tools to discriminate between communicative and other cognitive interactions (demarcation requirement), and it should be applicable to those mechanisms and phenomena investigated by means of synthetic models (operationability requirement).…”
Section: An Operational Approach To Communication: the Organisationalmentioning
confidence: 99%
“…A mix of theoretical and heuristic considerations converge in this branch of synthetic biology to pursue this goal. The result is an operational approach where the contents of hypotheses, definitions, and conceptual frameworks can inspire research and be used, manipulated, and tested in the laboratory [8].…”
Section: Introductionmentioning
confidence: 99%